Pedagogical and Psychological Foundations For Developing Professional Spiritual Culture Among Future Preschool Education Teachers - Khabibullaeva Sayyorakhon Makhamadali Qizi (Indonesian Journal Publisher, 2025)
The article highlights the issue of developing professional spiritual culture among future preschool education teachers. National and foreign research studies on the topic are analyzed, and the main directions of professional spiritual culture - personal potential, moral and ethical education, activity-based methods, and psychological factors - are identified. The necessity of a comprehensive and systematic approach is substantiated